Killing the Stereotype Of Women Leadership at Senior High School - ., Maharromiyati; ., Sumaryanto; Yuliana , Lia; Suhardiman , Sani (Journal of Ecohumanism, 2024)
This article explores the increasing attendance and impact of female principals, emphasizing the role in challenging stereotypes and changing educational leadership. Women leaders use a collaborative and empathetic style, fostering an inclusive and supportive school environment that enhances student engagement and academic performance. This study aims to assess the influence of women’s leadership philosophy on students and examine how gender dynamics and school culture are influenced by women’s leadership. Addressing gender stereotypes and inequalities in educational leadership is critical, as highlighted by this study. Using a quantitative design, data was collected from students and teachers through questionnaires to gain insights into the unique strengths of female principals in shaping educational environments. The study highlights the positive impact of female principals on academic achievement and school culture in high schools, attributing these results to their collaborative, empathetic, and student-centered leadership styles. The survey results revealed that 85% of teachers and 78% of students felt supported and motivated by female principals, who also effectively managed conflicts and created an inclusive environment. These findings underscore the importance of women’s leadership in education to foster a positive school atmosphere and improve academic performance.